1999
DOI: 10.1007/s004670050737
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and structure in patients with chronic renal failure

Abstract: The long-term consequences of cardiac alterations in children with chronic renal failure (CRF) and after renal transplantation (TX) are largely unknown. Studies in adults with end-stage renal disease (ESRD) assume that the fate of many pediatric patients is determined by a high cardiovascular morbidity and mortality. This review describes clinical manifestations, pathophysiology, cardiac function and structure, and management of heart disease in children with CRF and post transplant. Echocardiography and Doppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 78 publications
1
57
0
Order By: Relevance
“…Possible causes of right ventricular changes in patients undergoing HD may be uremia, fl uid retention, renal anemia, hyperparathyroidism, and high AV shunt fl ow [13][14][15]. Although RV works against low pressure in normal situations, it can adapt to high volume changes.…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes of right ventricular changes in patients undergoing HD may be uremia, fl uid retention, renal anemia, hyperparathyroidism, and high AV shunt fl ow [13][14][15]. Although RV works against low pressure in normal situations, it can adapt to high volume changes.…”
Section: Discussionmentioning
confidence: 99%
“…187 On the contrary, the results from a German study showed similar left ventricular mass index with both modes of treatment. 188 It is therefore likely that the prevalence of left ventricular in pediatric dialysis patients is more dependent on the overall control of BP and on volume status than on dialysis modality.…”
Section: Hypertension In Pediatric Dialysis Patientsmentioning
confidence: 99%
“…In pediatric patients who died in Europe on renal replacement therapy between 1987 and 1990, a cardiovascular cause of death was reported in 51% of dialyzed patients. [1] Although left ventricular systolic and diastolic dysfunction in adult patients has been reported, there has been limited data on cardiac functions in children with CRI and ESRD. [2] Few reports have examined whether hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) have different effects on the cardiac functions in children with ESRD.…”
Section: Introductionmentioning
confidence: 99%